A comparison of DIC-based techniques to measure crack closure in LCF. (December 2018) - Patriarca, L.; Foletti, S.; Beretta, S.
Graphical abstract: Highlights: Crack closure has a paramount importance in fatigue of metals. Digital Image Correlation was used to measure crack closure in Low Cycle Fatigue. Three techniques based on DIC were used to detect crack opening and closing levels. Improved ΔJeff calculation using crack closure stresses from DIC. Abstract: Crack closure is one of the most important phenomenon for the comprehension of fatigue behavior of metallic alloys. The effect of mean stress, overloads and variable amplitude loadings can be predicted modeling the crack closure in terms of opening and closing stress levels. Experimentally, the characterization of the crack closure in high and low cycle fatigue has gained large attention in the last fifty years. In fact, the proper detection of the opening and closing levels enhances the definition of a proper crack driving force and its modeling. This work primarily focuses on the measurement of the opening and closing stresses for cracks propagating in low cycle fatigue conditions. High-resolution full-field digital image correlation technique was adopted to track the crack profiles during cyclic loading and different approaches were adopted to analyze the displacement fields extracted with the virtual extensometers. The closure measurements were performed for three metallic alloys, different strain ranges (from elastic to dominant-plastic behaviors) and strain ratio to enlarge the field of applicability of the techniques presented.